1996
DOI: 10.1073/pnas.93.7.2879
|View full text |Cite
|
Sign up to set email alerts
|

CpG motifs present in bacteria DNA rapidly induce lymphocytes to secrete interleukin 6, interleukin 12, and interferon gamma.

Abstract: Bacterial infection stimulates the host to mount a rapid inflammatory response. A 6-base DNA motif consisting of an unmethylated CpG dinucleotide flanked by two 5' purines and two 3' pyrimidines was shown to contribute to this response by inducing polyclonal B-cell (3,4,(7)(8)(9)11). Recent work from our laboratory suggested that this B-cell stimulation was mediated by a 6-base nt motif consisting of an unmethylated CpG dinucleotide flanked by two 5' purines and two 3' pyrimidines (12). This motif is expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
844
1
6

Year Published

1998
1998
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,375 publications
(874 citation statements)
references
References 32 publications
23
844
1
6
Order By: Relevance
“…In vivo and ex vivo studies have shown that systemic delivery of CpG DNA stimulates immune cells to secrete a variety of proinflammatory chemokines and cytokines (7,15,16). To determine whether such treatment increases host susceptibility to arthritis, BALB/c mice were injected IP with 300 g of CpG DNA.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In vivo and ex vivo studies have shown that systemic delivery of CpG DNA stimulates immune cells to secrete a variety of proinflammatory chemokines and cytokines (7,15,16). To determine whether such treatment increases host susceptibility to arthritis, BALB/c mice were injected IP with 300 g of CpG DNA.…”
Section: Resultsmentioning
confidence: 99%
“…Unmethylated CpG motifs in bacterial DNA trigger an immune response characterized by the production of proinflammatory and Th1 cytokines (6)(7)(8)(9). This evolutionarily conserved response can protect the host from infectious pathogens (18)(19)(20), but it also increases the risk of developing autoimmune and inflammatory diseases (4,(21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bacterial DNA is a powerful stimulator of polyclonal proliferation in B cells and cytokine production by monocytes and lymphocytes. 20,21 These properties are attributed to unmethylated CpG motifs present in plasmid DNA or synthetic oligonucleotides, motifs which are much less frequent in mammalian DNA, which is not immunostimulatory. 22 These responses are sensitive to inhibitors of endosomal acidification, which is coupled to the generation of intracellular reactive oxygen species and the degradation of IkB.…”
Section: Adaptive Immunitymentioning
confidence: 99%